Impact of ongoing COVID-19 pandemic on child health and well being - Bashar, MD Abu; Begam, Nazia (Indian Journal of Child Health, 2020)
The pandemic of coronavirus disease-19 starting from Wuhan city of Hubei province in China has engulfed the entire world with adverse effects in terms of loss of human lives and stagnation in economies of most of the countries including the developed ones. One important aspect of this ongoing pandemic is its effect on children and their health round the globe. Apart from its direct effect in terms of morbidity and mortality caused by the illness itself, the indirect effect of the pandemic due to disruption of routine health services, closure of schools, isolation, and quarantining of the diseased and suspected persons, prolonged period of being indoors due to lockdown imposed by most of the countries which are having a more dreadful impact on children’s health and psychological well-being, which is an alarming sign.